2019
DOI: 10.1007/s00167-019-05723-9
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive reconstruction technique for chronic Achilles tendon tears allows rapid return to walking and leads to good functional recovery

Abstract: Purpose Chronic Achilles tendon tears, including chronic ruptures with end gap over 6 cm making end-to-end suturing impossible, can be treated with autologous hamstring graft reconstruction. The primary goal of this study was to present the biomechanical and long-term clinical results of recently developed minimally invasive Achilles tendon reconstruction technique. Methods Minimally invasive Achilles tendon reconstruction was applied to 8 foot and ankle cadaveric specimens as well as 18 patients with chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 37 publications
(69 reference statements)
1
21
0
Order By: Relevance
“…In group B, there was one case of Achilles tendon re-rupture (Table 2). The same results have also been reported by Bąkowski et al that patients who underwent traditional open techniques might be associated with a higher risk to develop the necrosis of skin and infection 10 . Furthermore, the pressure caused by the shortened Achilles tendon will act on the incision surface of conventional open operation, which may affect the healing of the incision, and increase the incidence of Achilles tendon exposure.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In group B, there was one case of Achilles tendon re-rupture (Table 2). The same results have also been reported by Bąkowski et al that patients who underwent traditional open techniques might be associated with a higher risk to develop the necrosis of skin and infection 10 . Furthermore, the pressure caused by the shortened Achilles tendon will act on the incision surface of conventional open operation, which may affect the healing of the incision, and increase the incidence of Achilles tendon exposure.…”
Section: Discussionsupporting
confidence: 85%
“…However, a 10-15cm longitudinal, slightly curved central skin incision would be created to operate the surgery, which will lead to severe trauma and a long postoperative scar on the skin of the posterior leg undoubtedly. On the other hand, various types of minimally invasive surgical approaches have been reported by many researchers for the treatment of NATR with good functional recovery and fewer complications 10,11 . Mafulli N and Piontek T et al also asserted that minimally invasive techniques may be advantageous compared with conventional open techniques since the latter is associated with a higher rate of postoperative infection 12,13 .…”
Section: Introductionmentioning
confidence: 99%
“…Bąkowski and colleagues performed biomechanical tests on reconstructed cadaveric Achilles tendons with the minimally invasive endoscopic technique using the hamstring tendon and showed encouraging results. All of the tested Achilles cadaveric specimens survived 2 loading blocks, that is, 250 cycles of 10 to 00 N load, followed by an additional 250 cycles of 10 to 200 N load 24…”
Section: Discussionmentioning
confidence: 99%
“…In our recent research we have shown that a minimally invasive, endoscopic Achilles tendon reconstruction using semitendinosus and gracilis tendons with Endobutton stabilization allows for good functional recovery [5,6]. As a logical consequence, the primary goal of the present study was to use a holistic approach for a comprehensive evaluation of Achilles tendon reconstruction results on multiple levels: clinical, functional and isokinetic.…”
Section: Introductionmentioning
confidence: 99%